14.0k views
1 vote
Simplify the following expression. Enter your answer in the form a^b.(5^2)^4 x 5^3=____

Simplify the following expression. Enter your answer in the form a^b.(5^2)^4 x 5^3=____-example-1
User Nihilarian
by
4.0k points

1 Answer

3 votes

To solve this question we will use the following properties:


\begin{gathered} A)\text{ (}a^m\text{)}^n=a^(m* n), \\ B)a^m* a^n=a^(m+n)\text{.} \end{gathered}

Applying property A) in the given expression we get:


(5^2)^4*5^3=5^(2\cdot4)*5^3=5^8*5^3\text{.}

Applying property B) in the above equation we get:


5^8*5^3=5^(8+3)=5^(11)\text{.}

Therefore:


(5^2)^4*5^3=5^(11.)

Answer:


5^(11)\text{.}

User Ilya Cherevkov
by
3.9k points